UJI EFEKTIFITAS KUNYIT PUTIH (CURCUMA SPP) TERHADAP PERTUMBUHAN ESCHERICHIA COLI - Qori Fadillah (Universitas Prima Indonesia, 2020)
Diarrhea is still a major cause of morbidity and mortality in infants and children. Diarrhea itself is still a major health problem in children under five, especially in developing countries such as Indonesia. Diarrhea is a common finding of Escherechia coli strains capable of causing bowel disease. Escherechia coli bacteria become pathogenic when found 107-108 gr / feses .. White turmeric is one of the most important types of zingiberacae family in traditional medicine and medicine industry. White turmeric has the main content of arilheptanoid compounds (kurkuminoid), essential oils with various monoterpenes and sesquiterpenes, and polysaccharides. Pharmacologic activity demonstrates the power of antimicrobial effects. then to prove it, the antimicrobial efetivity test was done in vitro with disc diffusion method (Kirby & Bauer test) against Escherichia coli which is gram negative bacteria swab method. White tomato juice (curcuma spp) is divided into concentrations of 100%, 75%, 50% and 25%. The results showed that white turmeric (curcuma spp) had potential as an anti bacterial in Escherichia coli.